Establishing expert consensus for the optimal approach to holistic risk-management in pulmonary arterial hypertension: a Delphi process and narrative review. (2nd November 2021) - Church, Colin; Gin-Sing, Wendy; Grady, Duncan; Johnson, Martin; Kiely, David G.; Lordan, Jim; Turner, Nadine; Wort, S. John; Condliffe, Robin
ABSTRACT: Background : Pulmonary arterial hypertension (PAH) is associated with significant morbidity and reduced life expectancy. Various medical therapies, together with non-medical therapies such as exercise training, have been shown to improve outcomes for patients. We performed a Delphi consensus process to establish optimal approaches to optimizing patient care. Methods : A steering group of PAH experts formulated 38 statements grouped into 6 themes: burden of PAH, risk-stratification, the role of clinical phenotyping in the management of PAH, assessing clinical response to treatment, maximizing the medical treatment pathway and the role of other management options. An online survey was sent to PAH health-care professionals throughout the UK to assess consensus with these statements. Consensus was defined as high if ≥70% and very high if ≥90% of the respondents agreed with a statement. A narrative review for each theme was then performed Results : Consensus was very high in 27 (71%) statements, high in 7 (18%) statements and was not achieved in 4 (11%) statements. Conclusions : Based on the consensus scores, the steering group derived 13 recommendations which, if implemented, should result in improved holistic care of patients with PAH.